Penelitian Sejarah Hukum Sipil di Indonesia - Khumarga, Dahnial (Pelita Harapan University, 2002)
The Indonesian Civil Law - which was derived from the Dutch one-is supposed to be the lee generalis of the (Indonesian) Commercial Law Respectively is supposedly the Business Law to the Civil Law as well Commercial Law. Take as example for instance the Law of contract. Which is the main source of the Business Law. Therefore its no eraggeration to say that a Business Law scholar thould be a